THE PROFESSIONALISM, COMPETENCE, ORGANIZATIONAL COMMITMENT & JOB SATISFACTION ON THE PERFORMANCE OF AUDITOR - Luthan, Elvira; Ali, Syahril; Hairaty, Ety (Fakultas Pendidikan Ekonomi dan Bisnis, 2019)
This study aimed to examine the effect of professionalism, competence, organizational commitment and job satisfaction on the performance of auditors at the public accounting firm (KAP) in Padang (6 Firms) and Medan (18 Firms) obtained by 96 respondens. This study was also conducted to determine if there are differences them. This research using primary data and sampling is done by purposive sampling method. The reasons for selecting different objects based on their differences in location and working environment on each KAP could cause differences mindset and worldview, values that are believed or how auditors work and indirectly led to differences in the understanding of how to generate performance the good one. The results of the analysis are the professionalism, competence and organizational commitment affect the performance of auditors, but job satisfaction has no influence on the performance of auditors. There is no difference among auditors in Padang and Medan because wherever auditor work then work will have the same standard, as set out in the professional ethics of auditors.